If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(-9) + -8y = -27 Multiply -5 * -9 45 + -8y = -27 Solving 45 + -8y = -27 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-45' to each side of the equation. 45 + -45 + -8y = -27 + -45 Combine like terms: 45 + -45 = 0 0 + -8y = -27 + -45 -8y = -27 + -45 Combine like terms: -27 + -45 = -72 -8y = -72 Divide each side by '-8'. y = 9 Simplifying y = 9
| 2x-9+1=3x-8-x | | 4x-3(12x-30)=18 | | 0.8n=0.9 | | 12x+12=6x | | 37/28=x/192 | | 2c+10=-12 | | X^2(x^2+22)=75 | | 2(6x+3)=3(4x+2) | | 37/28= | | 4a+7-9a-2= | | (8x+6)-3x=18 | | 3r-4=26 | | 2x-23=56 | | 7ln(x+8)-6lnx=0 | | -5x+6=-94 | | 9t-m^2t=0 | | 5x-25+15=0 | | 4+2k=-28 | | 4r=6r-1 | | 4+11d= | | 7-(4*4-10)+x=10 | | x^2-3xy+10=0 | | 8n^2+5-613=0 | | 2y+7=-9 | | 6r+2(4r-3)=8 | | 2y-9=2y+3 | | 14a=-8 | | x+1-2-(-2x+3)=x+5-(2-1) | | 7x^2-49x-14=0 | | 5x^2+2x=195 | | x+1-2-(-2x+3)=x+5-(2-1) | | 14b=-8 |